The Importance of Teaching Academic Reading Strategies to First-Year Multilingual Extended Degree Students at a South African University - Chimenya, Ulita Muidzo; Mpanza, Choice Dimakatso (Universal Education Jurnal Teaching and Learning, 2026)
The purpose of this paper is to report on the findings from a study that was conducted to investigate academic reading problems in a South African university among first-year multilingual extended degree students. The paper particularly explores if it is helpful to teach academic reading strategies to first-year extended degree students. A case study design and a qualitative research approach were used to collect and analyse data for this study. Interviews were used to collect data from two lecturers. Focus group discussions and an open-ended questionnaire were used to collect data from 48 students. The study found that it is beneficial to teach academic reading strategies to first-year extended degree students. Among others, summarizing, note-making and text evaluation skills were proven to be helpful. However, because of the low levels of reading proficiency among these students, more and continuous reading support needs to be provided. For this reason, we recommend establishing structured reading discussion programmes to coordinate additional academic reading platforms that can help enhance first-year students’ reading abilities.